The role of the androgen receptor in prostate development and benign prostatic hyperplasia: A review - Renee E. Vickman (Asian Journal of Urology, 2020)
Benign prostatic hyperplasia (BPH) is a benign enlargement of the prostate in which incidence increases linearly with age, beginning at about 50 years old. BPH is a significant source of morbidity in aging men by causing lower urinary tract symptoms and acute urinary retention. Unfortunately, the etiology of BPH incidence and progression is not clear. This review highlights the role of the androgen receptor (AR) in prostate development and the evidence for its involvement in BPH. The AR is essential for normal prostate development, and individuals with defective AR signaling, such as after castration, do not experience prostate enlargement with age. Furthermore, decreasing dihydrotestosterone availability through therapeutic targeting with 5α-reductase inhibitors diminishes AR activity and results in reduced prostate size and symptoms in some BPH patients. While there is some evidence that AR expression is elevated in certain cellular compartments, how exactly AR is involved in BPH progression has yet to be elucidated. It is possible that AR signaling within stromal cells alters intercellular signaling and a “reawakening” of the embryonic mesenchyme, loss of epithelial AR leads to changes in paracrine signaling interactions, and/or chronic inflammation aids in stromal or epithelial proliferation evident in BPH. Unfortunately, a subset of patients fails to respond to current medical approaches, forcing surgical treatment even though age or associated co-morbidities make surgery less attractive. Fundamentally, new therapeutic approaches to treat BPH are not currently forthcoming, so a more complete molecular understanding of BPH etiology is necessary to identify new treatment options.